Perceptions and knowledge of telemedicine in Ecuadorian practicing physicians: an instrument adaptation, validation and translation from English to Spanish - Geovanny Alvarado-Villa; Christian KuonYeng-Escalante; Nicolás Sagñay-Pinilla; Carlos Vera Paz; Ivan Cherrez-Ojeda (BMC, 2021)
Abstract Background During the COVID-19 pandemic, multiple countries have taken measures, such as isolation and quarantine, to prevent person-to-person spread of disease. These actions forced many physicians to adopt new techniques, such as telemedicine, to continue patient care, which has proven to be useful in continued care for those with non-COVID-19 pathologies. Various factors, such as security, confidentiality, cost-effectiveness, comfort, and the risk of malpractice, influence the perception of telemedicine among medical practitioners. The aim of this study was to adapt an existing instrument and validate it into a new Spanish version. The instrument is about the perceptions and knowledge of telemedicine in healthcare professionals. Methods The original questionnaire surveyed 6 domains with 40 questions, and each question was measured with a five-point Likert scale ranging from very high [5] to very low [1]. The survey was translated to Spanish using machine translation. The translation was reviewed independently, and then, a consensus was achieved regarding minor changes in the syntax of the survey to facilitate understanding. After expert feedback and questionnaire review, the research team members proposed reducing the instrument to 13 items in 4 domains due to the similarity of some questions. The sample was divided into 2randomly selected groups. Eligibility criteria included physicians providing private or public services with active medical/clinical practice. Results In total, 382 surveys were collected and separated into two random samples, S1 and S2 (198 and 184, respectively). In exploratory factor analysis (EFA), the 13 items were grouped into four theoretical domains, and item 7 presented cross loading between factors and was removed. Confirmatory factor analysis was performed to assess the scale reliability and interscale associations; three models were tested. Global Cronbach's alpha for internal consistency was 0.76 for the EFA. The goodness of fit measures root mean square error of approximation and comparative fit index were 0.009 and 0.999, respectively, for the best model. Conclusions The translated instrument was clear, with adequate internal consistency, readability, and appropriate for application in the physician setting. This validated questionnaire made it possible to evaluate physicians' knowledge of telemedicine to increase its use, especially during the COVID-19 pandemic.